ADHD Symptomatology and Perceived Stress Among French College Students. Issue 14 (December 2019) - Salla, Julie; Galéra, Cédric; Guichard, Elie; Tzourio, Christophe; Michel, Grégory
Objective: The objective of this study was to examine the independent association between inattention and hyperactivity/impulsivity symptoms and perceived stress among French college students.Method: Participants ( N = 6, 951) completed self-report surveys assessing ADHD symptoms, perceived stress, and sociodemographic characteristics. Multinomial logistic regression models were used to evaluate the association between ADHD symptoms and perceived stress.Results: Participants had a mean age of 20.8 years, and 75.6% were female. We found significant associations between increasing levels of inattention and hyperactivity/impulsivity symptoms and high level of perceived stress after adjustment for confounding variables. The association was stronger for inattention (odds ratio [OR] = 4.58, 95% confidence interval [CI] = [4.02, 5.22]) than for hyperactivity/impulsivity symptoms (OR = 1.21, 95% CI = [1.05 to 1.39]).Conclusion: Higher levels of inattention and hyperactivity/impulsivity were independently associated with perceived stress in French college students. This association was mainly driven by inattention. Screenings to better detect ADHD symptoms should be implemented in universities.